The Effect of Inflation and Interest Rate Spread on Real Sector Investment in Banda Aceh City: An ARDL Approach - Ulin Nur Arifah; Lidyana Dinda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Real sector investment plays a crucial role in generating employment, expanding production capacity, and strengthening regional economic structures. However, the impact of monetary indicators on investment can vary across regions, influenced by local business structures and financing characteristics. Banda Aceh City has an economic structure primarily dominated by trade, services, and small and medium enterprises, which may lead to an investment response to inflation and interest rate spread that does not align with national trends. This study investigates the effect of inflation and interest rate spread on real sector investment in Banda Aceh City during the 2010–2024 period. A quantitative approach is employed, utilizing 15 annual observations analyzed through the Autoregressive Distributed Lag (ARDL) model. The estimation results of ARDL (1,0,1) indicate that real sector investment exhibits a strong dependence on the value of investment from the previous period. Inflation and interest rate spread do not have a statistically significant effect, either in the short term or the long term. The F-Bounds results reveal the presence of a long-term relationship among the model's components. However, the adjustment coefficient is positive and not significant, indicating that the adjutment mechanism toward long-term equilibrium cannot be statistically confirmed. These findings imply that the variation in real sector investment in Banda Aceh City may also be influenced by structural and non-monetary factors not captured in the model, such as local demand conditions, access to financing, government spending, ease of licensing, and the overall business climate. Consequently, regional investment enhancement policies should focus more on improving the business climate, expanding access to financing, and supporting business actors, while maintaining inflation stability and banking intermediation efficiency as essential conditions. Future research is recommended to adopt a longer observation period and incorporate additional regional economic variables.